(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the trend of understanding phraseological units in a broad sense is followed, and units such as proverbs, sayings, aphorisms are included in phraseological units. The materials of English and Uzbek languages ​​are analyzed. It is noted that not all proverbs can be included in the phraseological units, and it is explained that they can be included in the phraseological units. At the same time, metaphors with a figurative character are expressed as proverbial phraseology.